Development of a Self-supporting Microporous Layer on a Metal Mesh for Carbon Backing-free Cathodes in Proton Exchange Membrane Fuel Cells - Joo, D.; Jin, S. M.; Jang, J. H.; Park, S. (WILEY-V C H VERLAG GMBH, 2018)
A self-supporting microporous layer (MPL) that is directly applicable to a metal mesh is developed, and its pore characteristics and surface morphology are investigated using scanning electron microscopy and mercury porosimetry. The PEMFC performance is evaluated according to the cathode flow field type and GDL configurations via polarization, AC-impedance spectroscopy, and 4-point probe measurements for the bulk resistance. The improvement in the polarization when using the MPL on the metal mesh is discussed in terms of the water management and electrical resistance at the cathode.
Keywords: HIGH CURRENT-DENSITY; GAS-DIFFUSION LAYER; FLOW-FIELD DESIGNS; WATER MANAGEMENT; BIPOLAR PLATES; PERFORMANCE; PEMFC; TRANSPORT; FOAMS